2011
DOI: 10.1002/andp.201000135
|View full text |Cite
|
Sign up to set email alerts
|

The maximal acceleration, extended relativistic dynamics and Doppler type shift for an accelerated source

Abstract: Based on the generalized principle of relativity and the ensuing symmetry, it has been shown that if the Clock Hypothesis is not true, there is a universal maximal acceleration am. We present here an extension of relativistic dynamics for which all admissible solutions will have have a speed bounded by the speed of light c and the acceleration bounded by am. An additional Doppler type shift for an accelerated source is predicted. The formulas for such shift are the same as for the usual Doppler shift with v/c … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 22 publications
0
47
0
1
Order By: Relevance
“…In section 3 we present possible explanations of the extra energy shift between emission and absorption lines, which, to the accuracy c -2 , is added to the shift caused by the relativistic dilation of time. In sub-section 3.1 we criticize a recent attempt to explain the inequality k>0.5 with the hypothesis about the existence of a universal maximal acceleration [15][16][17][18], and concurrently show that recent attempts to re-interpret the Mössbauer experiments in rotating systems [18,19] are, in fact, erroneous. In sub-section 3.2 we present a possible explanation of eqs.…”
Section: Introductionmentioning
confidence: 95%
“…In section 3 we present possible explanations of the extra energy shift between emission and absorption lines, which, to the accuracy c -2 , is added to the shift caused by the relativistic dilation of time. In sub-section 3.1 we criticize a recent attempt to explain the inequality k>0.5 with the hypothesis about the existence of a universal maximal acceleration [15][16][17][18], and concurrently show that recent attempts to re-interpret the Mössbauer experiments in rotating systems [18,19] are, in fact, erroneous. In sub-section 3.2 we present a possible explanation of eqs.…”
Section: Introductionmentioning
confidence: 95%
“…By acceleration, we mean the proper acceleration defined [12] as g = d 2 x/dtdτ , where τ is the proper time. In this case, it was shown in [13] that a Doppler type shift for an accelerated source will be observed. This Doppler type shift is similar to the Doppler shift due to the velocity of the source.…”
Section: Introductionmentioning
confidence: 86%
“…In W. Kündig experiment the absorber was exposed to a significant acceleration. In [13] it was indicated that the deviation of the shift in the experiment may be due to a longitudinal Doppler shift caused by the acceleration of the absorber. It led to an estimate of a universal maximal acceleration of order 10 19 m/s 2 and an indication of non-validity of the Einstein Clock Hypothesis [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different approach used Friedman et al [23] in 2010. Concerning the Čerenkov radiation, it is based on the fact that the speed of light in the medium with the index of refraction n is c/n.…”
Section: Pardy Journal Of High Energy Physics Gravitation and Cosmentioning
confidence: 99%